Off-farm work and food security status of farming households in Ghana. Issue 6 (18th August 2018) - Kuwornu, John K.M.; Osei, Evelyn; Osei-Asare, Yaw B.; Porgo, Mohamed
ABSTRACT: This study assessed the effect of participation in off-farm work on the food security status of farming households in the Northern Region of Ghana. Primary data were solicited from 324 farming households in the Tamale metropolis and Tolon district using semi-structured questionnaires. The treatment effects of both income and food security status were estimated using propensity score matching and double-robust methods. The empirical results suggest that participation in off-farm activities increased household daily calorie consumption. These results have implications for the development of off-farm ventures for the benefit of the farming households.